Phylogenetic Study of Piper L. (Piperaceae) Based on ITS Regions of nrDNA - Rani Asmarayani; Adi Pancoro (PTTI, 2002)
Studi filogenetik Piper L. (Piperaceae) berdasarkan daerah ITS DNA ribosomal inti.